An exploration of the support received by mothers for kangaroo mother care practice along the health facility-community continuum in a sub-district of Northern Karnataka, India - Maryann Washington; Leah Macaden; Prem K. Mony; Sumithra Selvam; Annetta Smith (PLoS ONE, 2025)
Introduction Early initiation with optimal duration of Kangaroo Mother Care (KMC), for all stable small babies (<2000grams at birth), is essential for accelerated reduction of neonatal mortality. The purpose of this paper is to explore the support received by mothers along the health facility-community continuum and its association with KMC practice. Methods All live small babies aged >  4 weeks of life, who were residing in the Gangawati sub-district, were recruited on a rolling basis (Dec 2017-Sept 2018) to obtain the estimated sample size of 210. Mother-baby dyads were visited in their homes to collect information [knowledge, attitude, and support received] for KMC initiation and maintenance till required. Secondary data on KMC duration was obtained from the district-wide project database. Results A total of 209 mothers with 227 small babies were interviewed (18 had twins). The mothers had a mean age of 23 (±4) years; and 7(±5) years of education, with 5 (±2) family members >  18 years in their households. More than half (51%) of the babies were female with a mean age of 35.6 (±7.5)days/ 4-6weeks and mean birth weight of 1693.6 (±221.4)grams irrespective of gestational age; 21.6% of whom were ≤ 1500g at birth. Most of the babies 205 (90.3%) were initiated on KMC at the health facility. The score obtained for KMC initiation [45%} and KMC maintenance support at the health facility [51.3%] was minimal. Multiple regression linear analysis showed that overall KMC support at the health facility was significantly higher for first-time mothers [β coefficient -1.54 (95% CI -2.87, -0.22)] and better knowledge scores on KMC [β coefficient 0.21 (05% CI 0.01, 0.42)]. KMC maintenance support was significantly higher for first-time mothers [β coeff -3.62 (95% CI -6.29, -0.96)] and for mothers whose babies had lower birth weights [β coeff -4.27 (95% CI -7.50, -1.05)]. Conclusion Mothers require support to initiate and continue KMC along the health facility-community continuum (S1 Table). The role of support at home would require further exploration to determine its association with KMC practice.